PENGEMBANGAN PANTAI WISATA BOMO KECAMATAN ROGOJAMPI KABUPATEN BANYUWANGI BERBASIS EDUKASI PEMBANGKIT LISTRIK ENERGI ALTERNATIF - Adi Pratama Putra; Gatut Rubiono; Rezki Nalandari; Megandhi Gusti Wardhana; Aan Mutowib (Jurnal Abdimas Bina Bangsa, 2023)
Bomo Beach in the Rogojampi sub-district, Banyuwangi district is one of the beaches managed by the local community as a tourist beach. This tourist beach has problems in the form of no electricity. This community service activity aims to develop Bomo tourist beaches based on alternative energy power generation education. The activity was carried out with management partners, namely the Kelompok Masyarakat Pengawas Perikanan (Pokmaswas) Benteng Samudra. Energy education activities are carried out by building energy houses equipped with solar panels as solar power generators (PLTS) and 2 windmills as wind power generators (PLTB). Implementation of activities provides benefits in the form of electricity supply that can be used as lighting and other needs. Activities provide the potential for new business development for the surrounding community and increase the number of visitors.